METHODOLOGY OF TEACHING ENGLISH AS A FOREIGN LANGUAGE IN MODERN EDUCATIONAL CONTEXTS - Abdisalimova Kamola Sanjar qizi (American Journals, 2026)
This article provides a comprehensive analysis of the methodology of teaching English as a foreign language (EFL) in contemporary educational contexts. The study examines the theoretical foundations, historical development, and modern approaches to English language teaching, with particular emphasis on communicative, learner-centered, and technology-enhanced methodologies. It explores major teaching methods such as Grammar-Translation, Audio-Lingual Method, Communicative Language Teaching, Task-Based Language Teaching, and Content and Language Integrated Learning. In addition, the article discusses the teaching of language skills, grammar and vocabulary instruction, assessment strategies, the integration of digital technologies, and the professional competencies required of English language teachers. Special attention is given to challenges faced in EFL contexts, including developing countries and post-Soviet educational systems. The article concludes with practical recommendations aimed at improving the effectiveness of English language teaching and enhancing learner outcomes.
Keywords: English language teaching, methodology, EFL, communicative approach, task-based learning, assessment, educational technology.